Deconstructing the causes of July sea level variability in the East Sea from 1994 to 2021 - Han, MyeongHee; Chang, Yeon S.; Yoo, Jeseon (Frontiers in Marine Science, 2023)
We propose several methods for deconstructing the causes of sea level change (SLC) in a semi-enclosed sea to find more important factors and discuss the important fluctuation of ocean mass transport divergence during a period of rapid sea level rise. In the 29 years from 1993 to 2021, the highest July sea level in the East Sea (Sea of Japan) was recorded in 2021 (65.09 cm), as well as the highest July sea surface and atmospheric temperatures. Based on satellite altimeter data in the East Sea, the SLC, as reflected in the absolute dynamic topography (ADT), which is the ADT difference between the last and first days of a month, was 7.18 cm in July 2021. This result may reflect a combination of oceanic and atmospheric factors: ocean heat transport divergence among the Korea/Tsushima, Tsugaru, and Soya Straits was found to contribute 2.32 cm of SLC, atmospheric heat flux at the sea surface contributed 2.87 cm of SLC, and mass divergence (including errors) accounted for 1.98 cm of SLC. The monthly mean sea level (ADT) variation in the East Sea must be investigated in terms of the oceanic and atmospheric fluxes in conjunction with SLC in ADT of previous months because the SLC in ADT in a previous month affects the sea level in the next month. Moreover, SLC sources can be divided into heat and others (mass + errors). In the period from 1994 to 2021, the relative contribution of heat to SLC was 97.4%. The comparatively small contribution by mass and errors had, however, large temporal fluctuations, as the standard deviation reached up to 96.7% of that of SLC in ADT. More accurate study about mass and error contributions to SLC needs in the near future.